Do migrant and resident species differ in the timing of increases in reproductive and thyroid hormone secretion and body mass? A case study in the comparison of pre-breeding physiological rhythms in the Eurasian Skylark and Asian Short-toed Lark - Lidan Zhao; Lijun Gao; Wenyu Yang; Xianglong Xu; Weiwei Wang; Wei Liang; Shuping Zhang (Avian Research, 2017)
Abstract Background Physiological preparation for reproduction in small passerines involves the increased secretion of reproductive hormones, elevation of the metabolic rate and energy storage, all of which are essential for reproduction. However, it is unclear whether the timing of the physiological processes involved is the same in resident and migrant species that breed in the same area. To answer this question, we compared temporal variation in the plasma concentration of luteinizing hormone (LH), testosterone (T), estradiol (E2), triiothyronine (T3) and body mass, between a migrant species, the Eurasian Skylark (Alauda arvensis) and a resident species, the Asian Short-toed Lark (Calandrella cheleensis), both of which breed in northeastern Inner Mongolia, China, during the 2014 and 2015 breeding seasons. Methods Twenty adult Eurasian Skylarks and twenty Asian Short-toed Larks were captured on March 15, 2014 and 2015 and housed in out-door aviaries. Plasma LH, T (males), E2 (females), T3 and the body mass of each bird were measured every six days from March 25 to May 6. Results With the exception of T, which peaked earlier in the Asian Short-toed Lark in 2014, plasma concentrations of LH, T, E2 andT3 of both species peaked at almost the same time. However, Asian Short-toed Larks attained peak body mass earlier than Eurasian Skylarks. Plasma T3 concentrations peaked 12 days earlier than plasma LH in both species. Generally, plasma LH, T, E2, T3 and body mass, peaked earlier in both species in 2014 than 2015. Conclusions The timing of pre-reproductive changes in the endocrine system and energy metabolism can be the same in migrant and resident species; however, residents may accumulate energy reserves faster than migrants. Although migration does not affect the timing of pre-breeding reproductive and metabolic changes, migrant species may need more time to increase their body mass. T levels in resident species may be accelerated by higher spring temperatures that may also advance the pre-breeding preparation of both migrants and residents.